Analysis of The Influence of Work-Life Balance and Job Stress on Turnover Intention Among Private Sector Employees of Generation Y in Jakarta - Nurul, Hanan; Yuniawan, Ahyar (Universitas Pendidikan Nasional, 2024)
This study was conducted to determine the importance of work-life balance and job stress in retaining Generation Y employees. The study had the objective of conducting an investigation on the relationship between work-life balance, job stress, and turnover intention among this demographic. A quantitative approach was used, utilizing Smart PLS version 4 for data analysis. The study involved 100 Generation Y employees as respondents. The findings revealed unexpected results. Contrary to the initial hypothesis, work-life balance had a positive and significant influence on turnover intention, leading to the rejection of H1. Job stress, as expected, showed a positive and significant impact on turnover intention, confirming H2. Surprisingly, work-life balance showed a positive and significant influence on job stress, resulting in the rejection of H3. The results of this study highlighted the complex dynamics between work-life balance, job stress, and turnover intention among Generation Y employees. The study concluded that work-life balance and job stress were important factors that influenced employee retention. The research suggested that management should focus on key aspects such as time allocation, compensation policies, and targeted efforts to effectively address these issues. The findings provided valuable insights for organizations looking to retain the Generation Y workforce in an increasingly competitive labor market.